2018
DOI: 10.1080/13548506.2018.1503692
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion and health-promoting lifestyle behaviors in college students

Abstract: Lifestyle choices play a major role in health outcomes. Hence, examination of factors associated with a healthy lifestyle is important for health promotion. Self-compassion is related to health behaviors but research on the role of self-compassion facets (self-kindness vs. self-judgment, common humanity vs. isolation, mindfulness vs. over-identification) on health behaviors is scarce. A total of 423 Turkish undergraduates completed Self-Compassion Scale and Health-Promoting Lifestyle Profile II. Health behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
8
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 15 publications
1
33
8
3
Order By: Relevance
“…The original English version of HPLP-II has been shown to be reliable, valid and stable across time based on previous studies [18,37]. It has been widely translated and used to measure health-promoting behaviour in different study populations [16,17,[38][39][40][41][42][43]. Although Malays comprise a significant proportion of the South East Asian population, there is a severe lack of validated tools in the Malay language to measure health-promoting behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The original English version of HPLP-II has been shown to be reliable, valid and stable across time based on previous studies [18,37]. It has been widely translated and used to measure health-promoting behaviour in different study populations [16,17,[38][39][40][41][42][43]. Although Malays comprise a significant proportion of the South East Asian population, there is a severe lack of validated tools in the Malay language to measure health-promoting behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…A self-compassionate MS patient would find it easier to accept his/her condition and show adaptive responses to disease-related problems, which in turn would enhance well-being and HRQoL (43). Previous studies showed that self-compassion is positively related to happiness, quality of life, optimism, positive affect, life satisfaction, and health promoting behaviors, while it is negatively associated with depression, anxiety, neuroticism, and negative affect in various samples including college students and HIV patients (27,28,30,32,33,(44)(45)(46). Thus, the current study aimed to compare self-esteem and self-compassion in their association with HRQoL dimensions in MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐compassion facilitates coping with negative life‐events, for example, stress and disappointment related to academic failure (Neely et al, 2009; Smeets et al, 2014). Self‐compassion protects against stress in these situations and is associated with well‐being (Fong & Loi, 2016; Gedik, 2019). Another aspect that is relevant to psychological well‐being is the difference between self‐compassion and self‐esteem.…”
Section: Introductionmentioning
confidence: 99%